Computer vision syndrome prevalence, knowledge and associated factors among Saudi Arabia University Students: Is it a serious problem? - Alrashidi, Sultan H.; Alhumaidan, H. (International Journal of Health Sciences, 2017)
Objectives: Computers and other visual display devices are now an essential part of our daily life. With the increased use, a very large population is experiencing sundry ocular symptoms globally such as dry eyes, eye strain, irritation, and redness of the eyes to name a few. Collectively, all such computer related symptoms are usually referred to as computer vision syndrome (CVS). The current study aims to define the prevalence, knowledge in community, pathophysiology, factors associated, and prevention of CVS. Methods: This is a cross-sectional study conducted in Qassim University College of Medicine during a period of 1 year from January 2015 to January 2016 using a questionnaire to collect relevant data including demographics and various variables to be studied. 634 students were inducted from a public sector University of Qassim, Saudi Arabia, regardless of their age and gender. The data were then statistically analyzed on SPSS version 22, and the descriptive data were expressed as percentages, mode, and median using graphs where needed. Results: A total of 634 students with a mean age of 21. 40, Std 1.997 and Range 7 (18-25) were included as study subjects with a male predominance (77.28%). Of the total patients, majority (459, 72%) presented with acute symptoms while remaining had chronic problems. A clear-cut majority was carrying the symptoms for <5 days and >1 month. The statistical analysis revealed serious symptoms in the majority of study subjects especially those who are permanent users of a computer for long hours. Conclusion: Continuous use of computers for long hours is found to have severe problems of vision especially in those who are using computers and similar devices for a long duration.